Mengembangkan Kompetensi Pedagogik Calon Guru Melalui E-Modif - Sulastri Sulastri; Sulikah Sulikah; Umi Nuraini; Verinta Dian Pitaloka (Universitas Negeri Surabaya, 2022)
The purpose of this research is to produce learning media products to develop the pedagogic competence of undergraduate accounting education students as prospective teachers. E-Modif (Flipbook-Based E-Modul) is a digital book that combines text, images, video, and audio for accounting lesson planning courses. The design of this study used the research design and development of the ADDIE model. The results of this study indicate that students not only find it easier to understand the concept of learning planning, but also can know E-Modif as a real example of 21st century learning media, so they can understand the material in a real context. E-Modif is an alternative choice of effective and attractive learning media, in accordance with 21st century learning, which can be applied in online learning. Students can access E-Modif through smartphones which makes it easier for them to study anytime and anywhere.